The Netherlands and the prohibition of nuclear weapons. Issue 1 (2nd January 2018) - Shirobokova, Ekaterina
ABSTRACT: On July 7, 2017, the United Nations conference to negotiate a legally binding instrument to prohibit nuclear weapons concluded with the adoption of the Treaty on the Prohibition of Nuclear Weapons (TPNW), which opened for signatures at the United Nations General Assembly two months later, on September 20. The nuclear-weapon states and their allies boycotted the negotiations with the sole exception of the Netherlands, which not only is a member of NATO, but also hosts US nuclear weapons on its territory. Domestic pressure and political traditions had significant effects on the Dutch government's decision to participate in the ban negotiations. The Netherlands negotiated in good faith, but its multilateralism and humanitarian considerations could not tip the scales in favor of joining the ban treaty. The government's commitment to a "step–by–step" approach to nuclear disarmament and maintenance of close cooperation with NATO determined the Dutch position on the new instrument. Despite staying outside the TPNW, the Dutch government shares the goal of nuclear-weapons elimination. This article also suggests a number of actions the Netherlands could take to advance nuclear disarmament.